The roles and targeting options of TRIM family proteins in tumor - Zhang, Yuxin; Zhang, Wenzhou; Zheng, Lufeng; Guo, Qianqian (Frontiers in Pharmacology, 2022)
Tripartite motif (TRIM) containing proteins are a class of E3 ubiquitin ligases, which are critically implicated in the occurrence and development of tumors. They can function through regulating various aspects of tumors, such as tumor proliferation, metastasis, apoptosis and the development of drug resistance during tumor therapy. Some members of TRIM family proteins can mediate protein ubiquitination and chromosome translocation via modulating several signaling pathways, like p53, NF-κB, AKT, MAPK, Wnt/β-catenin and other molecular regulatory mechanisms. The multi-domain nature/multi-functional biological role of TRIMs implies that blocking just one function or one domain might not be sufficient to obtain the desired therapeutic outcome, therefore, a detailed and systematic understanding of the biological functions of the individual domains of TRIMs is required. This review mainly described their roles and underlying mechanisms in tumorigenesis and progression, and it might shade light on a potential targeting strategy for TRIMs in tumor treatment, especially using PROTACs.